Anti-tyrosinase Activities of Curcumin-Chitosan Gold Nanoparticles Synthesized from Beetle (Oryctes rhinoceros) - Alyani Zainol Abidin, N.; Kormin, F.; Akhma Zainol Abidin, N.; Abu Bakar, M.F.; Chandra Iwansyah, Ade (Asian Journal of Chemistry, 2022)
A breakthrough in cosmeceuticals by utilizing insects as major ingredients in cosmetic products is gaining popularity. Therefore, the interest in rare sources of ingredients, for instance, from the Oryctes rhinoceros beetle, can bring huge benefit in turning pest to wealth. In this study, curcumin was chosen as the active ingredient loaded into chitosan-gold nanoparticles (CCG-NPs). However, curcumin is unstable, has poor absorption, a high rate of metabolism and high sensitivity to light. These are all factors that contribute to the lower bioavailability of any substance to reach the target cells. Therefore, chitosan extracted from O. rhinoceros acts as a drug carrier and incorported in gold nanoparticles are used to overcome these problems. The CCG-NPs were successfully synthesized at 70 ºC for 60 min under optimal conditions of reactant ratio of 2:0.5 (0.5 mM HAuCl4:0.1% curcumin). The tyrosinase enzyme inhibition of CCG-NPs from O. rhinoceros was 66.385 ± 3.0%. Thus showing a good inhibition trait for the anti-tyrosinase assay as it is almost double the tyrosinase inhibition percentage when being compared to CCG-NPs from the commercial chitosan. Therefore, CCG-NPs from O. rhinoceros has a high potential in cosmeceutical applications as whitening agent.